The upregulated scavenger receptor CD36 is associated with the progression of nontarget lesions after stent implantation in atherosclerotic rabbits - Li R; Cui S; Xu Y; Xing J; Xue L; Chen Y (Dove Medical Press, 2018)
Ruijian Li,1–3,* Sumei Cui,1–3,* Youshun Xu,4 Junhui Xing,5 Li Xue,1–3 Yuguo Chen1–3 1Department of Emergency, Qilu Hospital, Shandong University, Jinan, China; 2Key Laboratory of Emergency and Critical Care Medicine of Shandong Province, Qilu Hospital, Shandong University, Jinan, China; 3Key Laboratory of Cardiovascular Remodeling & Function Research, Chinese Ministry of Education & Chinese Ministry of Public Health, Qilu Hospital, Shandong University, Jinan, China; 4Qilu Medical College of Shandong University, Jinan, China; 5Department of Cardiology, First Affiliated Hospital of Zhengzhou University, Zhengzhou, China *These authors contributed equally to this work Background: The incidence of recurrent cardiovascular events from the progression of nontarget lesions (NTLs) is high for percutaneous coronary intervention-treated patients. However, the underlying mechanisms have not been thoroughly elucidated. Methods: In this study, ten atherosclerotic rabbits with multiple plaques in the upper and lower segments of abdominal aorta (group A) were randomly divided into two subgroups: group A1 underwent intravascular ultrasound examination and stent implantation in the lower segments of the abdominal aorta (n=5), whereas group A2 was without stenting (n=5). Group B was a control group without balloon injury. The serum levels of high-sensitivity CRP, interleukin-6 (IL-6), oxidized low-density lipoprotein, and CD36 were assessed via ELISA at five time points between the 10th and 18th weeks. The upper abdominal aorta was examined via the immunohistochemical stain and Western blotting of matrix metallopeptidase 9 (MMP-9), CD36, IL-6, and tumor necrosis factor α. Results: As a result, we found that stent implantation aggravated serum levels of CD36, oxidative stress, and inflammatory cytokines. Meanwhile, the upper abdominal arterial plaque burden significantly increased after stenting by intravascular ultrasound. Immunohistochemistry and Western blotting showed that the local NTLs’ matrix metallopeptidase 9, CD36, IL-6, and tumor necrosis factor α expressions in group A1 were significantly higher than those in groups A2 and B (P<0.05–0.01). More importantly, a strong correlation was identified between CD36 expression and NTLs’ plaque burden before the rabbits were killed. Conclusion: Taken together, stent implantation accelerated inflammation, induced oxidative stress, and increased the NTLs’ progression, which were associated with the upregulated CD36 expression. Keywords: inflammation, oxidative stress, CD36, atherosclerosis, stent